Investigation of Field-Based Molecular Evidence of Natural Transovarial Transmission of Babesia ovis in Rhipicephalus bursa and Rhipicephalus turanicus Ticks - Ulucesme, Mehmet Can; Aktas, Munir (John Wiley and Sons Ltd, 2025)
Babesia ovis is a tick-borne protozoan parasite that poses a significant threat to sheep production, particularly in endemic regions such as Türkiye. It is known to be transmitted by ixodid ticks through both transstadial and transovarial routes. This study was aimed at investigating the natural transovarial transmission potential of B. ovis in Rhipicephalus bursa and Rhipicephalus turanicus ticks under field conditions. A total of 751 adult ticks were collected from 84 small ruminants (41 sheep and 43 goats) in Elazığ Province, Türkiye. Following species identification, 85 fully engorged female R. bursa (n = 45) and R. turanicus (n = 40) were incubated under controlled conditions to allow oviposition. DNA was extracted from the female carcasses and their corresponding larval pools and analyzed using nested PCR targeting the 18S rRNA gene of B. ovis. The results revealed that B. ovis DNA was detected in 19.04% (8/42) of R. bursa females and in 7.89% (3/38) of R. turanicus females. Importantly, all larval pools derived from B. ovis-positive R. bursa females also tested positive, indicating natural transovarial transmission. In contrast, none of the larval pools from R. turanicus tested positive, despite the presence of B. ovis in the female carcasses. These findings suggest that R. bursa may serve as a competent natural vector and reservoir for B. ovis, whereas R. turanicus seems to possess less ability for vertical transmission of the parasite. Copyright © 2025 Mehmet Can Ulucesme and Munir Aktas. The Scientific World Journal published by John Wiley & Sons Ltd.
Keywords: Babesia ovis; natural transovarial transmission; Rhipicephalus bursa; Rhipicephalus turanicus; Türkiye